KONTROL MULTI MOTOR SERVO DENGAN JOYSTICK VIRTUAL BERBASIS ANDROID - I Gst Agung Mahendra Sedana Yoga; I Nyoman Piarsa; Putu Wira Buana (Jurnal Teknologi Informasi dan Komputer, 2025)
This research focuses on designing an Internet of Things (IoT)-based control system for multiple servo motors. The system is equipped with an Android-based controller using a virtual joystick, enabling online and real-time control. The use of a virtual joystick on an Android smartphone application allows operators to control the device remotely, enhancing safety and work efficiency, especially in hazardous or hard-to-reach areas. The objective of this research is to evaluate the success and accuracy of servo movements to ensure optimal performance. The findings aim to demonstrate that IoT technology can serve as a reference for implementing wireless control in various automated systems, improving operational quality in different applications. Experimental results show that joystick control via an Android device facilitates online operation and can be effectively utilized. However, hardware limitations, such as servo motors and brackets, reduce the accuracy of object transfer, leading to failure in some trials, with a success rate of 70 percent. Nevertheless, this research can serve as a reference for future developments in the field, particularly in enhancing the accuracy and stability of IoT-based control systems.